Implementation of the Financial Accounting Standards Statement 101 and Digitalization in the Financial Management of Al Ikhlas Mosque, Siantar District - Wirawan, Arya; Yenni Samri Juliati Nasution; Laylan Syafina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research aims to evaluate the effectiveness of the implementation of Statement of Financial Accounting Standards (PSAK) 101 and digitalization in the financial management of Al-Ikhlas Mosque in Siantar District. Accountable and transparent financial management is key to maintaining the trust of congregation members and supporting the mosque's operations sustainably. By using a descriptive qualitative approach and case study, data was collected through interviews, observations, and documentation. The results of the study indicate that the mosque management has not fully implemented PSAK 101 and is still using a simple manual recording system. Several key components in Islamic financial reports, such as the statement of financial position, cash flow, as well as the use of zakat and charity funds, have not been prepared. The level of digitization is still low due to limited technology literacy and human resources. Nevertheless, there is a commitment from the management to improve accountability through the openness of financial reports to the congregation. This research concludes that the implementation of PSAK 101 and digitization can significantly enhance the quality of financial governance in mosques. Therefore, training in Islamic accounting and the adoption of simple technologies are recommended as initial steps towards modern, accountable, and Sharia-compliant financial management.